Tshekatsheko-tsenelelo ya dipapadi tsa ntlha tse tlhano tsa ga D.P.S Monyaise - Malope, Recias Melato (My University, 1977)
Refer to the document
Thesis (M. A. Setswana)) -- University of the North, 1977
Keywords: Setswana language; Setwana novels; Novels -- History and criticism; D.P.S Monyase (Tswana novels) -- South Africa